Pengawasan Balai Besar Pengawas Obat Dan Makanan (BBPOM) Pada Kosmetik Di Kota Pekanbaru - Ompusunggu, Tati Prensesia; Meiwanda, Geovani (Peneliti.net, 2023)
The circulation of cosmetics that do not meet the regulations until now is still circulating in the Pekanbaru City area, The controlling form carried out by the Food and Drug Supervisory Agency in Pekanbaru is expected to be able to supervise the circulation of cosmetics and the circulation of cosmetic products must be in accordance with the provisions and must be safe for the public to use. The purpose of this study is to analyze the supervision of cosmetics circulating in Pekanbaru City by the Food and Drug Supervisory Hall in Pekanbaru, which is a non-ministerial government institution and works in the field of supervision of both medicine and food and knows what obstacles are encountered. The theory used is the supervision phase by Manullang, which contains three indicators: establishing standards, assessment rating, and assessment improvements. The Research Type is Qualitative Descriptive and performs data collection based on interviews and documentation. The conclusion of this study is that the supervision conducted by the Food and Drug Supervisory Hall on cosmetics was carried out but not optimal enough. The obstacles to cosmetic supervision in Pekanbaru are the lack of specificity of the division of labor duties in the examination section, the lack of participation in choosing the use of cosmetic products they use, the lack of attention in legal awareness, and the absence of cosmetic business operators so this can reduce the optimality of supervision carried out by the Food and Drug Supervisory Hall in Pekanbaru City.